Women in medicine through the ages / Le donne in medicina attraverso i secoli - Zuskin, E.; Pucarin-Cvetkovic, J.; Schachter, et al., E.N (La Medicina del Lavoro, 2008)
Background: Female practitioners of the medical arts have been active since the ancient world. The role of women in science, and particularly in medicine, has changed significantly over time. Methods: We provide a chronological review of the growing knowledge in medicine related to women’s activities through the ages with particular attention to occupational medicine. Throughout history hazards have been shaped by the forces that shape work itself, social evolution, shifting economic powers and demographic changes. Results: Mythical Greece, Egypt and ancient Rome were the cradle of ancient medicine. In the past century, women were allowed to enter the medical profession with increasing acceptance. Some of the most important women in ancient and modern medicine are recalled, such as Mother Peseshet in ancient Egypt, Artemisia of Caria and Phanostrate and Philista in the Greek period, Hildegard of Bingen, Marie Marguerite Biheron in England, Elisabeth Blackwell, Emily Jennings, Maude E. Abbott and others. Women in occupational medicine are described separately, such as Alice Hamilton, Harriet L. Hardy, Molly Newhouse and Olga Macek. Conclusions: Certainly, the first few women who iluminated the way for the generations that followed them into medicine, the women who made outstanding contributions to medicine, and the women who are currently finding success in medicine deserve our respect and admiration. Le donne in medicina attraverso i secoli Le donne che praticavano l’arte medica erano attive fin dai tempi antichi. Il ruolo delle donne nella scienza, in generale, e particolarmente nella medicina si è modificato in modo significativo nel corso del tempo. In questa presentazione, passiamo in rassegna cronologica la conoscenza medica sempre maggiore, il ruolo e l‘attività delle donne in medicina nel corso della storia, con particolare attenzione alla medicina del lavoro. Nel corso della storia, i rischi occupazionali derivavano dai determinanti del lavoro stesso: l’evoluzione sociale, l’alternanza dei poteri economici e le variazioni demografiche. La mitica Grecia, l’Egitto e l’antica Roma furono la culla della medicina antica. Nel corso del secolo scorso, alle donne è stato concesso di entrare nella professione medica con sempre maggiori consensi. Vengono citate alcune delle donne più rinomate della medicina, dai tempi antichi fino al presente periodo, come Madre Peseshet nell’Egitto antico, Artemisia di Caria e Fanostrate e Filiste nel periodo Greco, Hildegard von Bingen, Marie Marguerite Biheron in Inghliterra, Elisabeth Blackwell, Emily Jennings, Maude E. Abbott e altre. Vengono descritte separatamente le donne protagoniste della medicina di lavoro, come Alice Hamilton, Harriet L. Hardy, Molly Newhouse e Olga Macek. Senza dubbio, le prime donne che hanno illuminato la strada per le generazioni successive nella professione medica, le donne che hanno portato un contributo straordinario alla medicina e le donne che attualmente godono di successo, meritano il nostro rispetto e la nostra ammirazione.